Agriculture and food policy in Tunisia - Thabet B.; Boughzala M.; Ben Ammar B. (Food and agricultural policies in the Middle East and North Africa: Egypt, Lebanon, Morocco, Sudan, Tunisia, Turkey, 1994)
This paper provides an analytical description of the relevant economic environment within which agricultural activities are undertaken and of general sectoral characteristics and policies. In the presentation of this monograph, an attempt has been made to give a detailed picture of the agricultural and food sectors in Tunisia, including their potential as well as their problems. In regard to the agricultural sector, technical research suggests that resource mobilization and productivity growth are feasible. The structural economic adjustment package introduced in 1986 seems to have targeted real weaknesses in the economy. Yet, getting the economic system to function more smoothly and according to efficiency criteria will need serious investigation into real constraints on agricultural development; appropriate technologies, appropriate infrastructure, removal of real market distortions such as monopolies, change in public rhetoric toward producers and consumers and, above all, better economic discipline on the part of international trading partners. Social considerations that may be costly for governments to overlook will force real economic adjustment to take place only slowly.
Workshop on Food and Agricultural Policies in the Middle East and North Africa, 1993/07/05-07, Tunis (Tunisia)